Advances in fluid mechanics XII - Hernández, S. (Santiago), 1951-; Škerget, L.; Ravnik, J. (Jure) (WIT Press, 2019)
Containing papers from the 12th International Conference on Advances in Fluid Mechanics, this book covers a wide range of topics including basic formulations and their computer modelling as well as the relationship between experimental and analytical results. The emphasis is on new applications and research currently in progress.